Montage as a Plot-Forming Method in Vadim Levanov’s Dramaturgy - Zhurcheva, Tatiana (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The article is devoted to the issue of montage as a plot-forming technique actively used in modern drama. The possibilities of montage are considered on the basis of the last plays by Vadim Levanov. Levanov is one of the most famous representatives of the modern Russian drama of the turn of the 21st century, and his work reflected all the variety of ideological and artistic explorations in contemporary drama. The dramatic diptych The Life of the Holy Blessed Xenia of St. Petersburg and The Most Possibly Authentic and Plausible Biography of the Bloody Lady Darya Saltykova, a Moscow Hereditary Noblewoman as well as A Play about Cows undoubtedly were Levanov’s programmatic works which reflected his philosophical queries. The article shows how the use of the montage technique allowed the playwright to express his attitude towards the eternal opposition of good and evil.